A method for preparing microwave sintered oil-based rock debris residue ceramsite proppant

Through microwave sintering technology and admixture optimization process, the problems of uneven heating and high energy consumption in the preparation of oil-based rock debris residue ceramsite proppant have been solved, and the effect of low-cost and efficient preparation of ceramsite proppant has been achieved.

CN117247282BActive Publication Date: 2025-01-24SOUTHWEST PETROLEUM UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311207453.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-01-24
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

When using oil-bed rock debris residue to prepare ceramide proppants, there are problems such as uneven heating, high energy consumption, and low product performance, and the cost is high, so it is impossible to achieve coordinated consumption of solid waste and save raw material costs. Purpose.

Method used

The microwave sintering technology is used to prepare oil-based rock crumbs residual ceramic support agents. By adding ZRO2 and LIF as an outer agent, optimizing raw material formulas and process processes, including air flow grinding grinding, spray drying-powerful mixture machine joint particles, microwave sintering method, etc. Essence

Benefits of technology

The low-cost and efficient preparation of ceramic grain support agents has the advantages of a short sintering cycle, low energy consumption, uniform heating and high performance, and meet the requirements of SY/T 5108-2014 standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005154092710000091
    Figure GDA0005154092710000091
  • Figure GDA0005154092710000101
    Figure GDA0005154092710000101
  • Figure GDA0005154092710000111
    Figure GDA0005154092710000111
Patent Text Reader

Abstract

The present invention provides a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant. The ceramsite proppant prepared by the method has the advantages of low preparation cost, low energy consumption in the preparation process, and high roasting efficiency; the crushing rate, acid solubility, turbidity, and sphericity under 69MPa all meet the specification requirements of SY / T 5108-2014. The method achieves the problem of large-scale accumulation of oil-based rock debris residues by preparing a green, environmentally friendly, simple process, low energy consumption, and high resource utilization rate ceramsite proppant, and can also effectively reduce the problem of excessively high application cost of ceramsite proppant in the existing shale gas exploitation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the fields of petroleum, environmental protection and building materials, and specifically is a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant. Background Art

[0002] At present, China's shale gas exploration and development is in a stage of rapid development. In the large-scale development of shale gas, solid waste formed by the adhesion of oil-based drilling fluid and rock debris is inevitably produced, which is called "oil-based rock cuttings". Oil-based rock cuttings are a kind of hazardous waste generated during the drilling process of oil and gas fields. Its composition is very complex, usually composed of impurities such as petroleum hydrocarbons, drill cuttings, water, and macromolecular organic matter. These components make oil-based rock cuttings have certain biological or chemical toxicity. The petroleum hydrocarbon pollutants in them are extremely difficult to be degraded in the environment, and have a great impact on the ecological environment. Thermal desorption treatment technology has become the only large-scale industrialized oil-based rock cuttings disposal solution for oil fields due to its high recovery efficiency of oil substances and low pollution risk in the treatment process. However, the pyrolysis residue of oil-based rock cuttings after thermal desorption treatment still retains a small amount of petroleum hydrocarbons and some heavy metal ions, so its environmental risk has not been completely eliminated. Improper treatment of oil-based rock cutting residues will cause environmental safety risks such as waste of land resources, enrichment of pollutants, and leaching and leakage of heavy metals. Therefore, there is an urgent need to find a green, economical, high-cutting-volume, and high-resource utilization method to realize the resource processing of oil-based rock cuttings residues.

[0003] When exploiting resources, in order to ensure the smooth progress of oil and gas exploitation operations, it is usually necessary to inject proppants into the fracturing fluid. A good quality proppant can not only withstand strong closure stress, but also has excellent fracture conductivity. At present, ceramsite proppants are mainly used when selecting proppants for oil and gas exploitation in my country. Compared with quartz sand proppants, ceramsite proppants have better hardness, sphericity, corrosion resistance and other properties, and can better meet the requirements of oil and gas exploitation. The raw materials of ceramsite proppants are generally aluminum-containing minerals, industrial waste, etc., and by adding some auxiliary ingredients and performing specific processing, a high-temperature, high-pressure and low-density proppant is formed. Therefore, the development of a method for preparing ceramsite proppants using shale gas oil-based rock debris residues can achieve the harmless, economical, large-volume and high-resource utilization of oil-based rock debris residues, while expanding the comprehensive utilization of oil-based rock debris residues and reducing the cost of shale gas fracturing operations.

[0004] Patent CN202110476448.0, a Chinese patent entitled "A method for preparing proppant production raw materials using oil-based rock cuttings", discloses a method for preparing proppant production raw materials using oil-based rock cuttings, comprising the following steps: (1) determination and quantitative characterization of oil-based rock cutting components; (2) separation and collection of heavy component BaSO4; (3) separation and collection of heavy component magnetic minerals; (4) supplementation of skeleton materials; (5) addition of pore formers; (6) ball milling and mixing. The invention can process oil-based rock cuttings into low-density proppant production raw materials and recover BaSO4, achieving harmless treatment and resource utilization of oil-based rock cuttings, reducing the risk of environmental pollution of oil-based rock cuttings and the production cost of proppants. Patent CN1067473761A, a Chinese patent entitled "A ceramsite proppant with oleophilic properties and its preparation method", discloses an invention of a ceramsite fracturing sand with oleophilic properties, using different proportions of oil-based drill cuttings residue, potassium feldspar, bauxite, and bentonite after thermal analysis, and also by adding a small amount of waste glass powder to improve the performance of the ceramsite fracturing sand, and by loading the aluminate coupling agent, the prepared ceramsite fracturing sand has oleophilic properties. The ceramsite fracturing sand with oleophilic properties described in the invention has the characteristics of high compressive strength, low density, high closure pressure, and low permeability, and the sintering temperature of the ceramsite proppant is relatively low, ranging from 1040 to 1260°C, which can achieve the effect of low crushing rate while saving energy.

[0005] In the investigation of the above background, it can be found that there are a small number of public data on the preparation of ceramsite from oilfield waste. However, in all the studies on the preparation of ceramsite proppants using oil-based waste, most of them directly use oil-based rock cuttings as the raw materials for the preparation of proppants, and use traditional muffle furnace heating and sintering to prepare ceramsite proppants. The preparation process has problems such as uneven heating, high energy consumption, and low product performance. In addition, most of the constituent materials of the proppant except rock cuttings are non-industrial solid waste, so the cost is usually high, and it is impossible to achieve the purpose of synergistically absorbing solid waste and saving raw material costs. In view of this, this patent uses microwave sintering technology to prepare oil-based rock cutting residue ceramsite proppants. Microwave sintering technology is a process in which the sample absorbs energy by relying on the loss of the absorbing medium, that is, the raw materials are coupled with microwaves at the microscopic scale, and heat is generated from the inside of the sample to heat the object. Microwave sintering can effectively reduce the activation energy required for the reaction, reduce the sintering temperature, accelerate the sintering process, and shorten the sintering time and energy consumption. In order to achieve rapid microwave sintering, ZrO2 sand and proppant raw material balls are mixed in a mass ratio of 1:1 to ensure that the proppant can be heated evenly. At the same time, this patent combines the preparation process with the optimization of material properties. By introducing ZrO2 and LiF as additives, ZrO2 is used as an absorber and a nucleating agent. In addition to reducing the occurrence of uneven sintering of materials during the sintering process and avoiding damage to material properties caused by thermal stress, it can also effectively reduce the activation energy required for sintering and increase the sintering rate. It can also act as a nucleating agent and flux, synergistically with Fe2O3 in the material, accelerate the nucleation rate of the matrix at high temperature, facilitate the precipitation of corundum and barium feldspar, and promote the growth of matrix strength. The added LiF acts as a nucleating agent to promote the precipitation of barium feldspar in the sample. Finally, low-grade bauxite, oil-based rock residue, waste aluminum ash, coal gangue, and hydrometallurgical manganese slag were used to analyze the mineral composition of the oil-based rock residue. The bulk density of the prepared proppant was 1.17-1.34 g / cm 3 , apparent density is 2.31~2.62g / cm 3 When the acid solubility is 2.0-4.1%, the turbidity is 20-60FTU, the sphericity is >0.9, and the crushing rate is 2.3-5.1% at 69MPa. The above properties all meet the requirements of SY / T5108-2014 standard. Summary of the invention

[0006] In order to solve the problem of large-scale accumulation of oil-based rock debris and avoid the problems of uneven heating, high energy consumption, and low product performance in the sintering process using a traditional muffle furnace, the present invention proposes a method for preparing a microwave sintered oil-based rock debris ceramsite proppant. The ceramsite proppant prepared by the method has the advantages of low preparation cost, low energy consumption in the preparation process, and high roasting efficiency; the crushing rate, acid solubility, turbidity, and sphericity under 69MPa all meet the standard requirements of SY / T 5108-2014. The method achieves the problem of large-scale accumulation of oil-based rock debris by preparing a green, environmentally friendly, simple process, low energy consumption, and high resource utilization rate ceramsite proppant, and at the same time can effectively reduce the problem of excessively high application cost of ceramsite proppant in the existing shale gas extraction process.

[0007] The technical scheme of the present invention is: adding low-grade bauxite, waste aluminum ash, coal gangue, and hydrometallurgical manganese slag, coordinating the treatment of oil-based rock debris residue, grinding the raw materials through the airflow mill pretreatment process, achieving the refinement and homogenization of the raw materials, and improving the reaction activity, while using the spray drying-strong mixer combined granulation. The proportion of each component of the ceramsite proppant is recorded by dry mass as follows: oil-based rock debris residue: 40-60 parts, low-grade bauxite: 10-20 parts, waste aluminum ash: 30-40 parts, coal gangue: 5-10 parts, hydrometallurgical manganese slag: 10-15 parts, wherein the raw material formula is optimized by adding ZrO2 and LiF, which effectively promotes the development of the strength of the ceramsite proppant. In addition, in order to obtain a ceramsite proppant with better performance (the feature of the present invention), a microwave sintering method is used to realize the rapid and efficient preparation of the ceramsite proppant. And ZrO2 sand is used as an auxiliary heating material to reduce sintering energy consumption, accelerate sintering speed, shorten sintering cycle, and improve uneven temperature distribution during resistance furnace sintering. In summary, the present invention successfully sintered a ceramsite proppant with corundum and celsium feldspar as the main crystal phases through raw material ratio, mineral composition design, raw material ball preparation, gradient sintering and step-by-step cooling design.

[0008] Effects of the Invention

[0009] Oil-based rock debris residue: 40-60 parts, low-grade bauxite: 10-20 parts, waste aluminum ash: 30-40 parts, coal gangue: 5-10 parts, hydrometallurgical manganese slag: 10-15 parts; the ceramsite proppant prepared by the spray drying-strong mixer combined granulation method has the characteristics of controllable particle size, high sphericity and low particle shape coefficient; it is calcined by microwave sintering, so that it has the characteristics of short sintering cycle and low sintering energy consumption during the preparation process, and zirconia is used as a heating material to avoid excessive thermal stress and uneven sintering in the sample. The final prepared proppant has a volume density of 1.17-1.34g / cm 3 , apparent density is 2.31~2.62g / cm 3When the acid solubility is 2.0-4.1%, the turbidity is 20-60FTU, the sphericity is >0.9, and the crushing rate is 2.3-5.1% at 69MPa. The above properties all meet the requirements of SY / T 5108-2014 standard.

[0010] Compared with the prior art, the present invention has the following advantages:

[0011] (1) The present invention proposes a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant, in which a jet airflow mill is mainly used to grind and homogenize the proppant raw material mixture; the raw materials are weighed according to the ratio and placed in the crushing chamber, and the material is subjected to the action of high-speed airflow to obtain huge kinetic energy, causing high-speed collision and violent friction between the material particles in the crushing chamber, and at the same time, the shearing effect of the high-speed airflow on the material is utilized to achieve material crushing; under the impact of the high-speed airflow, the material particles collide with each other, so that the powder is fully mixed to achieve the purpose of material homogenization. The powder obtained by the grinding method has the advantages of smooth surface, regular particle shape, high activity and good dispersibility;

[0012] (2) The present invention proposes a spray drying-powerful mixer combined granulation process, which first uses a spray drying granulator to nucleate ceramsite proppant green balls, then puts the nucleated particles into a powerful mixer, adds atomized water and green powder to adjust the green ball particle size and polishes the green balls, and uses this method to ensure that the green balls have uniform quality, high sphericity, and high balling efficiency;

[0013] (3) The present invention proposes a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant, in which the microwave sintering method is mainly used to prepare the ceramsite proppant. The microwave sintering method mainly relies on the dielectric loss of the material itself to absorb microwave energy, that is, it couples with microwaves at a microscopic scale to generate heat from the inside to heat the object. The coupling effect of microwaves and materials can convert the electromagnetic energy of microwaves into thermal energy, and all the electromagnetic energy absorbed by the material can be used for self-heating. It has the advantages of less energy loss and high utilization rate, and can save about 80% energy compared with traditional sintering methods. In addition, microwave sintering technology controls the temperature rise and fall by controlling the incident power of the input device. In the closed metal furnace cavity, only the heated material can absorb microwaves to generate heat. The air and furnace body in the furnace cavity basically do not heat up, and the thermal inertia is relatively small, so selective heating is possible;

[0014] (4) The present invention proposes a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant, in which ZrO2 is added as a nucleating agent, a flux and an absorber. When ZrO2 is used as an absorber, it is a mixed absorber and has a thermal shock performance at a high temperature of 1000°C, which can increase its dielectric loss sharply at high temperature and generate heat. It can not only significantly improve the uneven sintering of the material and avoid the damage to the material performance caused by thermal stress, but also effectively reduce the activation energy required for sintering and reduce energy consumption. ZrO2, as a nucleating agent, synergizes with the iron oxide in the material to accelerate the nucleation rate of the matrix at high temperature, which is beneficial to the precipitation of corundum and celsium feldspar, thereby promoting the development of matrix strength.

[0015] (5) The present invention proposes a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant, using ZrO2 sand as a microwave heating auxiliary material, and mixing ZrO2 sand and proppant raw balls in a mass ratio of 1:1. This is because the dielectric loss of ZrO2 increases dramatically at high temperatures and generates heat. The heat energy generated by ZrO2 sand is used to heat the proppant raw balls, so that the sample can be heated evenly. When the mass ratio of ZrO2 sand to proppant raw balls is too large, it is easy to cause a waste of ZrO2 sand and reduce the sintering rate of the proppant; when the mass ratio is too small, the contact area between ZrO2 sand and proppant raw balls is reduced, which significantly reduces the heating rate and the prepared proppant has poor performance;

[0016] (6) The present invention provides a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant, in which LiF is added as a nucleating agent. + It can destroy the integrity of the glass network structure, reduce the viscosity of the liquid phase, and reduce the sintering temperature of the sample. At the same time, fluorine will replace the oxygen in -Si-O to become -Si-F. The network breaking effect of fluorine ions will promote the development of the glass structure from layered to short-chain. At the same time, the non-bridging bonds reduce the degree of polymerization of the glass network, making it easier for the silicon-aluminum structure to transform from two-dimensional to three-dimensional, promoting the formation of barium feldspar;

[0017] (7) The present invention proposes a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant, wherein the raw material thereof comprises 90% industrial solid waste, the product has high added value, and the preparation cost is low. The prepared proppant has a volume density of 1.17 to 1.34 g / cm 3 , apparent density is 2.31~2.62g / cm 3 When the acid solubility is 2.0-4.1%, the turbidity is 20-60FTU, the sphericity is >0.9, and the crushing rate at 69MPa is 2.3-5.1%. The above properties meet the requirements of SY / T 5108-2014 standard;

[0018] (8) The present invention provides a method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant, wherein the main mineral components are celsium feldspar, corundum and zirconium oxide.

[0019] Description of the accompanying tables and graphs

[0020] Figure 1 Table 1 is the technical specifications of various embodiments. Figure 2 , 3 are the XRD patterns of each example; Figure 4 The SEM image is under the optimal conditions; Figure 5 A microwave sintering furnace; Figure 6 The specific implementation method will be described below in conjunction with the attached table and figures. Specific implementation methods

[0021] In order to better understand the present invention, the present invention is further described in detail below in conjunction with examples, but the content of the present invention is not limited to the following embodiments.

[0022] Example 1

[0023] In this example, the weight proportions of raw materials (in dry state) are as follows: oil-based rock debris residue: 55 parts, low-grade bauxite: 10 parts, waste aluminum ash: 30 parts, coal gangue: 5 parts, hydrometallurgical manganese slag: 10 parts, ZrO2 powder: 2 parts, LiF powder: 1 part. The specific steps are as follows:

[0024] a. Grinding: According to the designed material ratio, weigh the corresponding oil-based rock debris, low-grade bauxite, waste aluminum ash, coal gangue, and hydrometallurgical manganese slag and put them into the jet mill. Use nitrogen as the grinding medium, set the grinding chamber pressure to 0.6-1MPa, and grind at a frequency of 20-40Hz for the sorting wheel. Place the ground sample in an electric blast drying oven and dry it to constant weight at 105±5℃.

[0025] b. Raw material mixing and granulation: according to the material ratio, 0.2-1.0 parts of corn starch, 1-4 parts of ZrO2, 2-5 parts of LiF, 70-90 parts of proppant powder and water are weighed to prepare a solution with a content of 50%-60%, and the mixed raw material solution is placed in the centrifugal atomizer of the dryer, and the steam valve and the high-pressure air pump valve are opened. After the material temperature reaches the predetermined temperature, the spray program is started to make the powder aggregate into nuclei; then the collected nucleated particles are poured into a high-power mixer and atomized water and green body powder are added to prepare proppant raw material balls. After the raw material balls grow to a diameter of 0.425mm-0.850mm, the high-power mixer is stopped, and finally the green balls of the target particle size are placed in an electric hot air drying oven and dried to constant weight at a temperature of 105±5°C.

[0026] c. Calcination: Place the prepared raw material balls into a microwave sintering furnace for calcination, and mix the zirconium oxide particles as auxiliary heating materials with the raw material balls in a mass ratio of 1:1. The sintering system is: heating from 400℃ to 500℃ at a rate of 30℃ / min, and keeping at 500℃ for 10min, then heating from 500℃ to 700℃ at a rate of 30℃ / min, and keeping at 700℃ for 10min, then heating from 700℃ to 950℃ at a rate of 20℃ / min, and keeping at the final sintering temperature for 30min.

[0027] d. Cooling: After the calcination, the ceramsite proppant in a high temperature state is cooled by a heat preservation and slow drop method, from 950°C to 700°C at a rate of 1-5°C / min, and then the temperature is reduced to 400°C at a rate of 1-3°C / min after it drops to 700°C, and then cooled to room temperature by furnace cooling.

[0028] e. Performance evaluation: After taking out the ceramsite proppant product, the sphericity, turbidity, bulk density, apparent density, breakage rate at 69 MPa and acid solubility of the sample were tested respectively.

[0029] According to SY / T 5108-2014 "Test Method for Proppant Performance in Hydraulic Fracturing and Rock Filling Operations", the bulk density of ceramsite proppant (kg / m 3 ), acid solubility (%), crushing rate at 69MPa (%), apparent density (kg / m 3 ), turbidity (FTU), sphericity are: 1.34kg / m 3 ,4.10%,5.10%,2.62kg / m 3 、57.6FTU、0.92.

[0030] Example 2

[0031] The weight proportions of the raw materials in this example are the same as those in Example 1.

[0032] The sintering schedule was as follows: the temperature was increased from 400°C to 500°C at a rate of 30°C / min and kept at 500°C for 10 min, the temperature was increased from 500°C to 700°C at a rate of 30°C / min and kept at 700°C for 10 min, the temperature was increased from 700°C to 1000°C at a rate of 20°C / min and kept at the final sintering temperature for 30 min.

[0033] According to SY / T 5108-2014 "Test Method for Proppant Performance in Hydraulic Fracturing and Rock Filling Operations", the bulk density of ceramsite proppant (kg / m 3 ), acid solubility (%), crushing rate at 69MPa (%), apparent density (kg / m 3), turbidity (FTU), sphericity are: 1.29kg / m 3 ,3.65%,4.59%,2.51kg / m 3 、53.7FTU、0.93.

[0034] Example 3

[0035] The weight proportions of the raw materials in this example are the same as those in Example 1.

[0036] The sintering schedule is as follows: the sintering schedule is: heating from 400°C to 500°C at a rate of 30°C / min, and keeping at 500°C for 10 min, heating from 500°C to 700°C at a rate of 30°C / min, and keeping at 700°C for 10 min, heating from 700°C to 1050°C at a rate of 20°C / min, and keeping at the final sintering temperature for 30 min.

[0037] According to SY / T 5108-2014 "Test Method for Proppant Performance in Hydraulic Fracturing and Rock Filling Operations", the bulk density of ceramsite proppant (kg / m 3 ), acid solubility (%), crushing rate at 69MPa (%), apparent density (kg / m 3 ), turbidity (FTU), sphericity: 1.20kg / m 3 ,2.94%, 3.58%, 2.43kg / m 3 、45.2FTU、0.93.

[0038] Example 4

[0039] The weight proportions of the raw materials in this example are the same as those in Example 1.

[0040] The sintering schedule was as follows: the temperature was increased from 400°C to 500°C at a rate of 30°C / min and kept at 500°C for 10 min, the temperature was increased from 500°C to 700°C at a rate of 30°C / min and kept at 700°C for 10 min, the temperature was increased from 700°C to 1100°C at a rate of 20°C / min and kept at the final sintering temperature for 30 min.

[0041] According to SY / T 5108-2014 "Test Method for Proppant Performance in Hydraulic Fracturing and Rock Filling Operations", the bulk density of ceramsite proppant (kg / m 3 ), acid solubility (%), crushing rate at 69MPa (%), apparent density (kg / m 3 ), turbidity (FTU), sphericity are: 1.17kg / m 3 ,2.00%,2.30%,2.31kg / m 3、20.0FTU、0.94.

[0042] Example 5

[0043] The weight proportions of the raw materials in this example are the same as those in Example 1.

[0044] The sintering schedule was as follows: the temperature was increased from 400°C to 500°C at a rate of 30°C / min and kept at 500°C for 10 min, the temperature was increased from 500°C to 700°C at a rate of 30°C / min and kept at 700°C for 10 min, the temperature was increased from 700°C to 1050°C at a rate of 20°C / min and kept at the final sintering temperature for 15 min.

[0045] According to SY / T 5108-2014 "Test Method for Proppant Performance in Hydraulic Fracturing and Rock Filling Operations", the bulk density of ceramsite proppant (kg / m 3 ), acid solubility (%), crushing rate at 69MPa (%), apparent density (kg / m 3 ), turbidity (FTU), sphericity are: 1.22kg / m 3 ,2.87%, 3.78%, 2.49kg / m 3 、43.9FTU、0.92.

[0046] Example 6

[0047] The weight proportions of the raw materials in this example are the same as those in Example 1.

[0048] The sintering schedule was as follows: the temperature was increased from 400°C to 500°C at a rate of 30°C / min and kept at 500°C for 10 min, the temperature was increased from 500°C to 700°C at a rate of 30°C / min and kept at 700°C for 10 min, the temperature was increased from 700°C to 1050°C at a rate of 20°C / min and kept at the final sintering temperature for 45 min.

[0049] According to SY / T 5108-2014 "Test Method for Proppant Performance in Hydraulic Fracturing and Rock Filling Operations", the bulk density of ceramsite proppant (kg / m 3 ), acid solubility (%), crushing rate at 69MPa (%), apparent density (kg / m 3 ), turbidity (FTU), sphericity: 1.30kg / m 3 ,3.49%, 4.26%, 2.54kg / m 3 、52.2FTU、0.91.

[0050] Example 7

[0051] The weight proportions of the raw materials in this example are the same as those in Example 1.

[0052] The sintering schedule was as follows: the temperature was increased from 400°C to 500°C at a rate of 30°C / min and kept at 500°C for 10 min, the temperature was increased from 500°C to 700°C at a rate of 30°C / min and kept at 700°C for 10 min, the temperature was increased from 700°C to 1050°C at a rate of 20°C / min and kept at the final sintering temperature for 60 min.

[0053] According to SY / T 5108-2014 "Test Method for Proppant Performance in Hydraulic Fracturing and Rock Filling Operations", the bulk density of ceramsite proppant (kg / m 3 ), acid solubility (%), crushing rate at 69MPa (%), apparent density (kg / m 3 ), turbidity (FTU), and sphericity are: 1.33kg / m 3 ,3.97%, 4.76%, 2.60kg / m 3 , 60FTU, 0.90.

[0054] Table 1. Technical indicators of various implementation examples

[0055]

[0056]

[0057]

[0058] It can be seen from Table 2 that, in addition to the oil-based rock debris residue, the raw materials contain a large amount of other industrial solid wastes, thus having the effect of synergistically absorbing solid wastes and reducing the production of raw materials; at the same time, the proppant raw materials adopt a gas flow mill homogenization treatment process under protective gas conditions, and through a special microwave sintering process, it has the effect of saving sintering time (only 60 to 100 minutes) and improving sintering quality, achieving high efficiency and energy saving effects. Compared with other public patents, the prepared proppant has lower crushing rate and acid solubility, and has outstanding technical and performance advantages.

Claims

1. A method for preparing microwave sintered oil-based rock debris residue ceramsite proppant, characterized in that: The main steps include: S1 Place the crushed oil-based rock debris, low-grade bauxite, waste aluminum ash, coal gangue, and hydrometallurgical manganese slag in an electric blast drying oven and dry them at 105±5℃ to constant weight; weigh the corresponding oil-based rock debris, low-grade bauxite, waste aluminum ash, coal gangue, and hydrometallurgical manganese slag according to the material ratio, put them into a jet mill, use nitrogen as the grinding medium, set the grinding chamber pressure to 0.6~1MPa, and grind at a sorting wheel frequency of 20~40Hz; place the ground sample in an electric blast drying oven and dry it at 105±5℃ to constant weight; S2 Mix the dried powder with zirconium oxide (ZrO2), lithium fluoride (LiF), corn starch, and 95-100°C water, and stir continuously to form a raw material mixture or suspension containing 50%-60% solids; S3 Spray drying-strong mixer combined granulation: put the mixed raw material solution into the centrifugal atomizer, open the steam valve and the high-pressure air pump valve, and start the spray program after the material temperature reaches the predetermined temperature to make the powder aggregate into nuclei; then pour the collected nucleated particles into the strong mixer and add atomized water and green body raw powder. After the raw material balls grow to a diameter of 0.425mm~0.850mm, the strong mixer stops working, and finally the raw material balls of the target particle size are placed in an electric heating blast drying oven and dried at 105±5℃ to constant weight; S4 Segmented calcination: The prepared proppant raw material balls and auxiliary heating material ZrO2 sand are mixed evenly in a mass ratio of 1:1, put into a crucible, and calcine the proppant in a microwave sintering furnace; the sintering system is: heating from 400℃ to 500℃ at a rate of 30℃ / min, and keeping at 500℃ for 10min, then heating from 500℃ to 700℃ at a rate of 30℃ / min, and keeping at 700℃ for 10min, then heating from 700℃ to 950~1100℃ at a rate of 20℃ / min, and keeping at the final sintering temperature for 20~60min; S5 Cooling: The ceramsite proppant in a high temperature state after roasting is cooled by the heat preservation slow drop method, from 1100℃ to 700℃ at 1~5℃ / min, and then to 400℃ at 1~3℃ / min after the temperature drops to 700℃, and then cooled to room temperature by furnace cooling.

2. The method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant according to claim 1, characterized in that: In step S1, the ingredients are as follows according to the mass fraction: 40-60 parts of oil-based rock debris residue; 10-20 parts of low-grade bauxite; 30-40 parts of waste aluminum ash; 5-10 parts of coal gangue; and 10-15 parts of hydrometallurgical manganese slag. Corn starch: 0.2~1 parts; ZrO2: 1~4 parts; LiF: 2~5 parts.

3. The method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant according to claim 1, characterized in that: The ceramsite proppant has a crushing rate of 2.3-5.1% at 69 MPa and a bulk density of 1.17-1.34 g / cm 3 , apparent density is 2.31~2.62g / cm 3 , acid solubility is 2.0~4.1%, turbidity is 20~60FTU, and sphericity is >0.

9.

4. The method for preparing a microwave sintered oil-based rock debris residue ceramsite proppant according to claim 1, characterized in that: The ceramsite proppant is formed with a matrix structure mainly composed of barium feldspar and corundum phases and containing zirconium oxide microcrystals.

Citation Information

Patent Citations

  • Method for preparing proppant production raw material from oil-based rock debris

    CN113278410A

  • Harmless treatment method and harmless treatment device for industrial petroleum wastes

    CN105414155A

  • Proppants with carbide and / or nitride phases

    WO2009012455A1